2014
DOI: 10.1039/c4ra11737a
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized mesoporous silica material and anionic dye adsorption: MCM-41 incorporated with amine groups for competitive adsorption of Acid Fuchsine and Acid Orange II

Abstract: Adsorption of two representative anionic dyes (Acid Fuchsine (AF) and Acid Orange II (AO)) using MCM-41 functionalized with amine groups in a mesoporous silica framework (NH2–MCM-41) as the adsorbent was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 72 publications
(70 reference statements)
5
30
0
1
Order By: Relevance
“…The adsorption kinetics is clearly modeled better by the pseudo-second-order kinetic model, which has higher correlation coefficient values (R 2 > 0.998) and theoretical equilibrium adsorption capacities closer to the experimental values in MO solutions with different initial concentrations. Similar kinetic behavior was also observed in adsorption of dye onto other adsorbents such as layered double hydroxide (LDH) [39], mesoporous silica [46], activated clays [47], and carbon [41]. It is also found that k 2 decreases with increasing initial MO concentration.…”
Section: Adsorption Kineticssupporting
confidence: 57%
“…The adsorption kinetics is clearly modeled better by the pseudo-second-order kinetic model, which has higher correlation coefficient values (R 2 > 0.998) and theoretical equilibrium adsorption capacities closer to the experimental values in MO solutions with different initial concentrations. Similar kinetic behavior was also observed in adsorption of dye onto other adsorbents such as layered double hydroxide (LDH) [39], mesoporous silica [46], activated clays [47], and carbon [41]. It is also found that k 2 decreases with increasing initial MO concentration.…”
Section: Adsorption Kineticssupporting
confidence: 57%
“…The increase in ΔG 0 values with the increase in temperature demonstrates a negative effect of temperature on adsorption. Moreover, negative ΔS 0 values indicate a reduction in the randomness at the solid-liquid interface during the adsorption [30,43]. Furthermore, the results of adsorption thermodynamics agree well with the equilibrium isotherms obtained in this study, and the optimal reaction temperature was 25˚C.…”
Section: Adsorption Thermodynamicssupporting
confidence: 86%
“…Total number of scans for 31 P, 29 Si and 13 C were 512, 512 and 1810, respectively. The Spectrum two FT-IR spectrophotometer (Perkin-Elmer) was used to record FT-IR spectra in the range of 450 to 4000 cm -1 using KBr pellet.…”
Section: Characterizationmentioning
confidence: 99%
“…[26][27][28] Among these, adsorption of these pollutants by solid porous adsorbents seems more feasible, versatile, efficient, economical and very importantly free from secondory pollutants. [29][30] In this article, we report the sonochemical synthesis of cyclophosphazene bridged mesoporous organosilicas. These high surface area cyclophosphazene bridged mesoporous organosilicas (CPMOs) were then used for removal of organic dyes and Cr(VI) ions in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%